Enhanching Students’ Writing Achievement through E-Mail Exchanges on Personal Letter - Nurhasanah Nurhasanah; Shofiyatul Huriyah (Universitas PGRI Semarang, 2019)
The objective of this study was to find out whether or not there is any significant differences between teaching writing the eight grade students by using e-mail exchanges and those who are not. The method of this study was quasi experimental non-equivalent control group design. The total number of population was 278 students. The sample was class VIII.1 and VIII.2 were classified into two groups, experimental and control group. The data were collected through test. The test was writing test, namely pretest and posttest, and the results were analyzed by t-test by helping SPSS (Statistical Package for the Social Sciences), the data were obtained from the pretest of the experimental group. The pretest was given before giving the treatment, and posttest after the treatment. It The writing test was about personal letter written by the students based on one of topics that they preferred. Based on the data analysis, the mean score of the posttest in the experimental group is 43.7500 and the mean in the control group is 25.9659. It means the mean score of the posttest in the experimental group is higher than the mean in the control group. The result of independent sample t-test shows that t-obtained is higher than the critical value of t-table is 16.780 > 1.664. It could be concluded that there is any significant improvement in personal letter writing between the students who are taught by using E-mail exchanges and those who are not.